Proteomics annotate therapeutic properties of a traditonal Tibetan medicine – Tsantan Sumtang targeting and regulating multiple perturbed pathways. (2nd April 2016) - Zhou, Yi; Li, Zhanqiang; Tang, Feng; Ge, Rili
Abstract: Ethnopharmacological relevance: Tsantan Sumtang is a traditional Tibetan medicine, which has been traditionally used as medicine for the treatment of cardiopyretic disease which is similar to angina. However, the precise and comprehensive mechanism of it pretreatment remain elusive, so in this study, we used proteomics to systematically analyse the therapeutic mechanism of it. Materal and methods: Rats were divided into three groups ( n =6): Tsantan Sumtang group (2 g/kg), the model group, the control group (distilled water, 10 ml/kg). Drugs were treated once a day for 20 days. After the last administration of drug, left anterior descending coronary artery ligation in vivo was performed. 5 days latter, the hearts were harvested and we applied HPLC- MS/MS using an isobaric TMTs proteomics technology to analyse the differentially expressed proteins among groups. Results: We comfirmed from the data that 752 proteins were differentially expressed in model group when compared with the control group, 314 proteins showed the recovery of the values by Tsantan Sumtang treatment. The differential proteins were analysed by gene ontology, cellular pathways and clustering analyses, most of them were metabolic enzymes. These included glycolytic enzymes, enzymes implicated in fatty acids oxidation and the tricarboxylic acid cycle, various subunits of different mitochondrial electron transfer chain complexes, as well as enzymes involved in antioxidation system. Conclusion: Tsantan Sumtang can target and regulate multiple metabolic perturbed pathways, especially it can partially inhibite fatty acid β-oxidation, stimulate glucose metabolism, oxidative phosphorylation and ATP utilization to protect the injured heart. This helped us to understand the molecular therapeutic mechanisms of Tsantan Sumtang on mycardial ischemia. Graphical abstract: